A generalized, pruritic, papulo-vesicular eruption in an infant: An uncommon presentation of Gianotti Crosti Syndrome - Sandhu, Jaspriya; Garg, Shriya; Gupta, Sunil; Garg, Bhavna (Journal of Pakistan Association of Dermatologists, 2022)
A 1- year- old boy was brought by his parents with a 2-week-history of skin colored to erythematous crusted, papulo- vesicles distributed symmetrically over face, extremities and prominent truncal involvement. Lesions were intensely pruritic, disrupting the child’s sleep; an episode of upper respiratory tract infection (URTI) preceded the eruption. A skin biopsy was done keeping the differential of Gianotti Crosti Syndrome (GCS), Histiocytosis and Pityriasis lichenoides et varioliformis acuta (PLEVA); epidermis showed acanthosis, hyperkeratosis and follicular plugging, with scant perivascular lymphocytic infiltrate in the dermis. Emollients, topical steroids and antihistamines led to marked improvement at 1-week follow-up; on clinico- pathological correlation, a diagnosis of an Atypical GCS was made. To the best of our knowledge, such an atypical presentation of GCS has not been previously reported.